Legal Certainty On The Applicability Of The Minister Of Home Affairs Regulation No. 86/2017 in The Preparation Of Local Government Work Plans - Anak Agung Ngurah Bgs Pradhana Ningrat; I Wayan Rideng; I Ketut Kasta Arya Wijaya (Pemuliaan Keadilan, 2025)
This study examines Legal certainty is a crucial element in effective governance, especially in the context of laws and regulations. This research examines the enforceability of the Minister of Home Affairs Regulation No. 86/2017, which regulates the preparation of the Local Government Work Plan (RKPD). This research finds that legal certainty in the RKPD is strongly influenced by the implementation and supervision of the regulation. In addition, challenges in harmonization between central and local regulations are an important factor in ensuring effective enforcement. The results show that the ambiguity in Article 78 results in uncertainty in the integration of pokir into the RKPD, thus reducing the effectiveness of DPRD participation and potentially creating conflict between the executive and legislature. To improve legal certainty, it is suggested that further revision and explanation of the provision is needed, as well as training for local officials on more effective implementation of the regulation. The findings are expected to serve as recommendations for policymakers in drafting clearer and firmer regulations.This research recommends clarification and revision of Article 78 to create a clearer framework and support synergy between local governments and DPRDs. The findings are expected to contribute to the improvement of more inclusive and responsive regional planning policies.